Disconnectivity Social of Conflict in the Circle of Iron Ore Mine in Bone Regency, South Sulawesi, Indonesia - Samanlangi, Andi Ilham; Agustang, Andi; Adam, Arlin; Alim, Andi (International Journal of Criminology and Sociology, 2021)
Conflict is a common occurrence in mining activities that ignore the triple bottom line principle. Neglecting the impact of environmental damage and the welfare of the communities around the mine has resulted in social disconnection leading to conflict. This study aims to describe comprehensively the social disconnect in the iron ore mining project in Bontocani District so that mining conflicts do not occur. The research method used is a mixed-method with a sequential design starting with qualitative methods then followed by quantitative methods. The findings of this study indicate that the causes of social disconnect include: There are environmental impacts that damage the livelihoods of residents around the mine area, the company does not respect local wisdom, the role of government is not maximal as a mediator, The economic impact is in the form of loss of livelihoods in the agricultural sector which is exacerbated by road infrastructure. damaged and Social impact in the form of jealousy between residents. The practical implication of this research is the creation of a harmonious relationship between the government, companies and communities in mining management.